The curriculum ideology of the South African secondary school Biology - Lindelani Mnguni (South African Journal of Education, 2013)
South Africa has had a number of curriculum reforms since 1994 which have been based on both political and education grounds. However, there is a dearth of knowledge about the nature of the envisioned graduates, especially with respect to social challenges. This can be addressed by exploring the curriculum ideology which outlines the vision of subjects within an education system by clarifying the aims of the subject, the content knowledge taught, the instructional process, the roles ofteachers and students, as well as the assessment processes. There are at leastfour curriculum ideologies, namely, the scholar academic ideology, efficiency ideology, student-centred ideology and social reconstruction ideology. The aim of the current study was to investigate the curriculum ideology of the Grade 11 Biology curriculum by analysing the Curriculum and Assessment Policy Statement. Results show that Biology adopts a multi-curriculum ideology approach with greater emphasis on scholar academic and student-centred ideologies. Characteristics of the social reconstruction ideology were the least observed. This implies that Biology is designed to advance the discipline but will probably not lead to social and student empowerment with regard to current social challenges.